2000
DOI: 10.4141/a99-083
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of one-quarter Chinese Meishan and three-breed conventional cross females for sow productivity, and growth and carcass characteristics of the progeny

Abstract: M. 2000. Comparison of one-quarter Chinese Meishan and three-breed conventional cross females for sow productivity, and growth and carcass characteristics of the progeny. Can. J. Anim. Sci. 80: 281-286. The reproductive performance over five parities of two one-quarter Meishan female genotypes were compared with a three-breed cross female genotype based on conventional breeds of pigs. Hampshire-sired progeny from these females were evaluated for growth performance and carcass measures. The female genotypes eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2003
2003
2005
2005

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…Sinclair et al (1998b) reported that until day 16 of lactation, 50% Meishan sows make fewer posture changes, and spend more time lying with their udder exposed and less time standing than sows from European breeds. These results suggest a greater willingness to nurse, and could in part account for the lower piglet mortality in Meishan litters (Bidanel et al 1990; Van der Steen and de Groot 1992; Wolter et al 2000). In contrast, recent data show that 50% Meishan sows spend more time lying on the belly than Large White sows in late lactation (Farmer et al 2001), possibly to reduce access of piglets to teats.…”
Section: Sow and Piglet Behaviour Peripartum Behaviourmentioning
confidence: 66%
See 4 more Smart Citations
“…Sinclair et al (1998b) reported that until day 16 of lactation, 50% Meishan sows make fewer posture changes, and spend more time lying with their udder exposed and less time standing than sows from European breeds. These results suggest a greater willingness to nurse, and could in part account for the lower piglet mortality in Meishan litters (Bidanel et al 1990; Van der Steen and de Groot 1992; Wolter et al 2000). In contrast, recent data show that 50% Meishan sows spend more time lying on the belly than Large White sows in late lactation (Farmer et al 2001), possibly to reduce access of piglets to teats.…”
Section: Sow and Piglet Behaviour Peripartum Behaviourmentioning
confidence: 66%
“…Sinclair et al (1996) also demonstrated increased litter weights in 50% Meishan sows, but not in gilts. Recent results also suggest that in 25% Meishan females, the increase in litter size would not be accompanied by any negative effects on piglet or litter weights at birth (Young 1998;Wolter et al 2000). In addition, breeding Meishans to Yorkshire or Landrace boars would be more advantageous than breeding to Durocs.…”
Section: Sow and Litter Performancesmentioning
confidence: 92%
See 3 more Smart Citations